A case study on the application of passive control and seismic isolation techniques to cable-stayed bridges: A comparative investigation through non-linear dynamic analyses. (15th September 2015) - Martínez-Rodrigo, M.D.; Filiatrault, A.
Highlights: The possible retrofit and isolation of an existing cable-stayed bridge is numerically investigated in order to improve its dynamic performance. A nonlinear Finite Element model of the bridge is implemented including strength degradation capabilities. Suitable configurations with Fluid Viscous Dampers, Metallic Dampers, Tuned Mass Dampers and Friction Pendulum Bearings are designed and the bridge response is evaluated under far and near field records. Seismic performance indices are defined and used to compare the proposed innovative solutions. Conclusions regarding the most appropriate retrofit alternative are provided. Abstract: This paper investigates the seismic performance of an existing steel cable-stayed bridge located in a high seismic zone. In 1988 the structure experienced the failure of one of its anchorage plates needing closure and structural repair as a consequence of seismic activity. In this study, the possibility of retrofitting the original bridge with different passive supplemental damping and seismic isolation systems is proposed and assessed, in order to improve the response of the structure in its longitudinal direction. To this end a Finite Element model of the bridge is developed and the structural response is evaluated through non-linear dynamic response analyses under a set of historical ground motions of different intensities, including a near field record. Strength degradation capabilities are introduced in the model, allowing the occurrence of brittle failure in all the members. Seismic performance indices referred to the dynamic response of the unretrofitted structure and to the results of a pushover analysis are defined and used to compare the proposed innovative solutions. The major improvement on the overall response of the bridge is shown and conclusions regarding the most appropriate retrofit alternative for the particular case study are determined.